Control of sinus venous valve and sinoatrial node development by endocardial NOTCH1 - Wang, Yidong (Cardiovasc Res, 2020)
AIMS: Sinus venous valve (SVV) and sinoatrial node (SAN) develop together at the sinoatrial junction during embryogenesis. SVV ensures unidirectional cardiac input and SAN generates sinus rhythmic contraction, respectively; both functions are essential for embryonic survival. We aim to reveal the potential role of endocardial NOTCH signalling in SVV and SAN formation. METHODS AND RESULTS: We specifically deleted Notch1 in the endocardium using an Nfatc1(Cre) line. This deletion resulted in underdeveloped SVV and SAN, associated with reduced expression of T-box transcription factors, Tbx5 andTbx18, which are essential for the formation of SVV and SAN. The deletion also led to decreased expression of Wnt2 in myocardium of SVV and SAN. WNT2 treatment was able to rescue the growth defect of SVV and SAN resulted from the Notch1 deletion in whole embryo cultures. Furthermore, the Notch1 deletion reduced the expression of Nrg1 in the SVV myocardium and supplement of NRG1 restored the growth of SVV in cultured Notch1 knockout embryos. CONCLUSION: Our findings support that endocardial NOTCH1 controls the development of SVV and SAN by coordinating myocardial WNT and NRG1 signalling functions.